Erysimum nasturtioides (Brassicaceae): a local endemic to the massif Kallar and Sabzkuh rediscovered after 154 years - Zeraatkar, Amin; Shirmardi, Hamzeh Ali (Phytotaxa, 2026)
Botanical exploration conducted in 2024 in Chaharmahal and Bakhtiari province, Iran, led to the collection of Erysimum nasturtioides Boiss. & Hausskn. in Boiss. (Brassicaceae), a narrowly endemic species first described in 1868. Since its original discovery, the species has not been reported or documented elsewhere. This study presents a more detailed morphological description, the first natural images, updated distributional data, phenological observations, ecological information, and an assessment of the conservation status of E. nasturtioides. A detailed comparative analysis is also presented comparing this species in relation to its closest relatives.